Pregunta
\[ f(x) = 3x + 4 \quad g(x) = 2x - 3 \] \[ \text{Find: } f \circ g(x) \]
Ask by Schultz Harper. in South Africa
Feb 02,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( f \circ g(x) = 6x - 5 \)
Solución
To find the composition \( f \circ g(x) \), we need to apply the function \( g \) first and then apply \( f \) to the result of \( g(x) \).
Given:
\[
f(x) = 3x + 4
\]
\[
g(x) = 2x - 3
\]
**Step 1: Compute \( g(x) \)**
\[
g(x) = 2x - 3
\]
**Step 2: Compute \( f(g(x)) \)**
\[
f(g(x)) = f(2x - 3) = 3(2x - 3) + 4
\]
\[
= 6x - 9 + 4
\]
\[
= 6x - 5
\]
**Final Answer:**
\[
f \circ g(x) = 6x - 5
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Mind Expander
To find \( f \circ g(x) \), we need to substitute \( g(x) \) into \( f(x) \). First, we have: \[ g(x) = 2x - 3 \] Next, we substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f(2x - 3) \] Now we plug \( 2x - 3 \) into \( f(x) = 3x + 4 \): \[ f(2x - 3) = 3(2x - 3) + 4 \] \[ = 6x - 9 + 4 \] \[ = 6x - 5 \] Therefore, the result is: \[ f \circ g(x) = 6x - 5 \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium